COMPARING THE DRYING CHARACTERISTICS OF APPLE AND KIWI FRUITS - Ozgen, Filiz (Vinca Inst Nuclear Sci, 2021)
In this study, the effects of drying air velocity on the organic apple and kiwi fruits that were sliced in same sizes were experimentally examined in a convective type dryer. In order to examine the effect of drying air velocity to drying process, drying air at 45 oC and 10% relative humidity was applied to kiwi and apple fruit samples sliced in 4 mm thickness at 0.5, 1.0, and 1.5 m/s drying air velocities. It was observed from the experimental results that drying air velocity has a significant effect on the total drying time. The drying time of apple and kiwi slices under these conditions varied between 150-360 minutes. The lowest drying time (150 minutes) was obtained at 1.5 m/s for the apple sample with 4 mm slice thickness, and the highest drying time (360 minutes) was obtained at 0.5 m/s for the 4 mm thick kiwi sample. Freshly collected products were successfully dried in a convective dryer at different velocities.
Keywords: drying; drying air velocity; apple; kiwi